The Role of Tourism in Islamic Da'wah - Mariam Bt Yaakob (Universiti Sains Islam Malaysia, 2011)
Tourism is an activity concerning about musafir, rihlah, siahah, hijrah, ziarah and riadah which include dealing in business, finding knowledge, preaching, enjoying the nature of environment, getting the information, health and recreation. In Malaysia, Tourism has become important for the economy the country and it is one of industries that contribute foreign exchange for Malaysia. The research done is based on field study to see the role of tourism in Islamic dakwah. This research is focuses on tourism agencies involved in tourism. The purpose of this study is to know the efforts in tourism sector in carrying out the preaching activity and to what extent in the tourism sector. To get the data, the method of questionnaires is used and the questionnaires are distributed to 40 respondents, mostly the staff of tourism agencies. The result shows there is an activity of dakwah that have performed by tourism agencies. The researcher also found that there is no effort that done by tourism sector to contribute in the dakwah activity.